The Behavior of Slab-Column Joints of Reactive Powder Concrete under Cyclic Load - Bambang Budiono; Awal Surono; Ivindra Pane; Ruddy Kurniawan (Institute for Research and Community Services, Institut Teknologi Bandung, 2016)
Experimental work on four specimens of reinforced concrete slab- column connection sub-assemblages using reactive powder concrete (RPC) was conducted. The specimens were subjected to a combination of gravity and cyclic loading. The gravity loading was represented by a number of concrete cubes hung on the slab bottom surface and the cyclic lateral loading was applied on the upper end of the columns. The specimens consisted of two variables, i.e tensile flexural reinforcement ratio (0.65% and 1.8%) and slab span (2.0 m and 3.0 m). Shear reinforcement was not used in the slab. The displacement history consisted of three repeated cycles, starting from 0.07 to 5.00 percent drift ratio, covering the elastic and the inelastic response of the specimens. The RPC mixture proportion for the specimen's material was developed using local materials and normal concrete technology methods. The average RPC compression tests results were 136.0 MPa at 28 days and 141.0 MPa at the time of the first specimen, tested at 56 days. The tests results showed that up to 5.0 percent drift all specimens had stable hysteresis loops without any significant degradation of strength and stiffness. The specimen with a larger tensile flexural reinforcement ratio developed more strength, stiffness and energy dissipation.